STUDI PRODUKSI ASAM LEVULINAT DARI PATI UBI GAJAH (Manihot esculenta) MENGGUNAKAN KATALIS ASAM SULFAT - Wisnu Aditya; Amir Awaluddin; Saryono ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
The utilization  of  Manihot esculenta  to produce  platform chemical such as    levulinic acid  (LA)    has  been  studied    in  detail to  optimize    the  LA  production. The  LA production from  Manihot esculenta  was  monitored  using    reaction times  of  the hidrolysis reaction (3-85 min.),    the reaction temperatures  (150˚C, 170˚C,  and 190˚C), and  concentrations  of sulfuric acid as the catalyst  (1%,  3%,  and 5%).  The  products obtained  were  then  characterized using  high performance  liquid  chromatography (HPLC)    to determine the contents of gl ucose,  hydroxymethylfurfural  (HMF)    and LA. The result showed that  the LA production increased with  the  rise    of temperature  and catalyst concentration, whereas the    glucose and HMF  production decreased with    the rise  of temperature and catalyst concentration. The highest  production    of LA reached approximately 50% (based  on initial concentration of biomass) at reaction temperature of 170˚C and 5% of sulfuric acid concentration for 70 minutes of reaction time.